Optimisation Models and Methods in Energy Systems - Antunes, Carlos Henggeler (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Challenging problems arise in all segments of energy industries—generation, transmission, distribution and consumption. Optimization models and methods play a key role in offering decision/policy makers better information to assist them in making sounder decisions at different levels, ranging from operational to strategic planning.